2021
DOI: 10.18502/ijph.v50i7.6623
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Hospitals Nurses’ Cognition on Palliative Care in Shandong Province, China: A Cross-Sectional Study

Abstract: Background: Palliative care is an essential part of medical practice, however, it has developed slowly in China. We aimed to analyze the current situations of the cognition on palliative care among the nurses in Shandong Province, China. Methods: This was a cross sectional study. Investigation of 1050 nurses came from 5 third-class hospitals and 5 second-class hospitals in Shandong Province, China from Jul to Oct in 2018. The questionnaire included 4 parts: general information of the subject, the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Focusing on the precise results obtained by the participants, an average percentage of correct answers in PCQN of 61.4% was found. These results are better than those obtained when piloting the Spanish version of the PCQN [ 52 ], a study conducted in Florida among pediatric nurses [ 61 ], a study to validate the French version of the PCQN [ 62 ], and those obtained in research conducted in countries where palliative care has very little development, such as Ethiopia [ 40 , 63 ], Saudi Arabia [ 64 ], Mongolia [ 65 ], China, [ 48 ] Nepal [ 51 ], Jordan [ 50 , 66 ], and Indonesia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Focusing on the precise results obtained by the participants, an average percentage of correct answers in PCQN of 61.4% was found. These results are better than those obtained when piloting the Spanish version of the PCQN [ 52 ], a study conducted in Florida among pediatric nurses [ 61 ], a study to validate the French version of the PCQN [ 62 ], and those obtained in research conducted in countries where palliative care has very little development, such as Ethiopia [ 40 , 63 ], Saudi Arabia [ 64 ], Mongolia [ 65 ], China, [ 48 ] Nepal [ 51 ], Jordan [ 50 , 66 ], and Indonesia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This fact is also identified in studies exploring educational needs in palliative care for both students and professionals. Indeed, both groups refer to the need for training in these psychosocial aspects of palliative care [ 16 , 23 , 48 , 49 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, randomized controlled trials have shown that specialist PC offered from basic symptom management to goals-of-care discussions 11,12 , which added onto usual oncologic care can improve quality of life, symptom control, patient and caregiver satisfaction, quality of end-of-life care, and possibly survival. 13 From the practical standpoint, it is important to recognize that oncologists and nursing staff often have very limited clinic time, making it di cult to address supportive care issues comprehensively 14,15 . They may also lack the interest, interdisciplinary teams, screening tools, and knowledge to provide state-of-the-art supportive care.…”
Section: Inpatient Palliative Carementioning
confidence: 99%